Análise dos efeitos hidrodinâmicos associados à resistência adicional em ondas - Souza Neto, Álvaro José (2019)
Since the added resistance in waves is associated with ocean navigation, it has a great economic, environmental and strategic importance. Hulls are usually designed according to resistance data in calm seas and therefore, they lose efficiency when encounter adverse environmental conditions. This research proposes the phenomenon investigation, through CFD methodology, into effects of shear stresses, vertical ship motions (radiation) and direct interaction between incident wave and hull (diffraction). The linear superposition principle and hypothesis of inviscid phenomena, adopted in the potential approach, are examined. The study includes analysis of RANS and Euler formulations in resistance simulations. A resistance test with a scaled hull, in head regular waves, is simulated. Restrictions are imposed on resistance simulations and hydrodynamic effects, isolated. Among others things, it was concluded that, for the wavelength similar to the ship length, the added resistance in waves is basically influenced by the vertical motions, the viscous effects can be neglected and the interaction between radiation and diffraction reduces the added force.